Radiographic and functional outcome of complex acetabular fractures: implications of open reduction in spinopelvic balance, gait and quality of life - Vitaliano F. Muzii; Giuseppe Rollo; Guido Rocca; Rocco Erasmo; Gabriele Falzarano; Francesco Liuzza; Michele Bisaccia; Giuseppe Pica; Raffaele Franzese; Luigi Meccariello (Medicinski glasnik, 2020)
Aim: To investigate the effects of surgical reduction of complex acetabular fractures on spine balance, postural stability and quality of life. Methods: Twenty-six patients with acetabular fractures surgically treated by open reduction and internal fixation were divided into two groups according to the amount of reduction. Group A consisted of 18 patients with satisfactory reduction (?2 mm), and group B of eight patients with incomplete reduction (>2 mm). Functional outcome was measured with Harris Hip Score (HHS), Oswestry Disability Index (ODI), and Short Form (12) Health Survey (SF12). Radiological parameters were assessed with standing whole spine, pelvis and hip X-rays, including pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), and sagittal vertical axis (SVA). Follow-up intervals were 1, 3, 6 and 12 months and annually thereafter. Gait analysis and baropodometry were performed after 24 months of operation. Results: Mean HHS, ODI, and SF-12 was improved during the first postoperative year in both groups. After two years average scores kept improving for group A, but worsened for group B. Mean PI, PT, and SS increased in both groups during the first postoperative year, with further increase after two years only in group B. After two years, 16 (89%) patients in group A and four (50%) in group B had a balanced spine (SVA <50 mm). Gait analysis and baropodometry showed greater imbalance and overload for group B compared to group A. Conclusion: In the long term, incomplete reduction of associated acetabular fractures may lead to poor outcome because of secondary spinopelvic imbalance, with posture and gait impairment.
Keywords: acetabulum; fracture; gait analysis; open reduction; postural balance